The influence of micelle formation on bile salt secretion. - O'Máille, E R (1980)
1. The influence of micelle formation on bile salt secretion was assessed by analysing the secretory characteristics of, and interaction between, the natural micelle-forming bile salts, taurocholate and cholate, and the artificial non-micelle-forming bile salts, taurodehydrocholate and dehydrocholate (both of which are subjected to reductive metabolism), in anaesthetized dogs. 2. Competitive secretory interaction between these two classes of bile salt was demonstrated thereby indicating that they share the same biliary transport system. Taurodehydrocholate had a lower affinity for the transport system than that of taurocholate and the metabolic derivatives of dehydrocholate. 3. The (initially determined) biliary secretory maxima for taurodehydrocholate (4 . 9 +/- 1 . 9 (S.D.) mumole/min. kg, n = 6) and total 'dehydrocholate' in taurine replete dogs (4 . 2 +/- 1 . 0 mumole/min. kg, n = 16) were both significantly less than those for taurocholate (8 . 0 +/- 1 . 8 mumole/min. kg, n = 16) and total cholate in taurine replete dogs (6 . 9 +/- 1 . 2 mumole/min. kg, n = 12). 4. The initially determined secretory maxima of taurodehydrocholate and 'dehydrocholate' were elevated by about 30 and 36%, respectively, by an earlier period of taurocholate administration; the most likely explanation (which is supported by independent morphological studies) for this effect is that taurocholate increases the number of functional 'carriers' in the canalicular membrane. When calculated for optimal conditions, the secretory maxima of the non-micelle-forming bile salts closely approached those of the micelle formers. 5. The above results would seem to indicate that micelle formation (in the hepatocyte, canalicular membrane or bile) is not essential for the effective translocation of bile salt by the specific canalicular membrane receptors. The results also suggest that the effective concentration of bile salt in bile (possibly 60--70 times greater in the case of the non-micelle-formers) is not an important determinant of the net secretory performance of conjugated bile salt. 6. At the same bile salt secretion rate (3 . 06 mumole/min. kg), the bile flow rate associated with taurodehydrocholate (44 . 3 +/- 2 . 7 (S.D. along regression line) microliter/min. kg, n = 38) was significantly greater than that associated with taurocholate (29 . 5 +/- 7 . 7 microliter/min. kg, n = 80) but significantly less than that associated with 'dehydrocholate' in taurine replete dogs (51 . 7 +/- 4 . 8 microliter./min. kg, n = 33), 'dehydrocholate' after acute taurine depletion (61 . 2 microliter./min. kg, n = 1) and free cholate after taurine depletion (49 . 8 +/- 9 . 8 microliter/min. kg, n = 92). The extra flow associated with the free bile salts is derived by means that are largely or entirely independent of their osmotic activity in bile.